Effect on The Quality of Passenger Satisfaction (Study in Radin Inten II Airport South Lampung) - Ardansyah ARDANSYAH; Stefanny Ellena Rushlan (Bandar Lampung University, 2015)
Radin Inten II airports managed by PT Angkasa Pura 2 is one example of a company that offers its services in the field of aviation. To face the competition in the business environment services, airports are required to always improve the quality of care services by considering what the needs and expectations of service users. Problems in this study is: Does Quality Service Passenger Satisfaction Influences on RadinInten II Airport South Lampung? The purpose of this study was to analyze the effect of quality of service to the airport passenger satisfaction In Radennten II South Lampung. Methods of data analysis in this study using simple linear regression. Based on test results obtained R² value of 0.380, which means that 38% of passenger satisfaction (Y) aircraft flight services are located in airports Radin Inten II influenced by the variable quality of service. While the remaining 62% is influenced by other variables not examined in this study. Based on test results obtained statistics is positive constant value of 2.858 states that if there is no activity of the independent variables (quality of service) which affect passenger satisfaction, the satisfaction of passengers is positive. X marked positive regression coefficient of 0.895 states that if the variable quality of service increased by 1 point, then the passenger satisfaction will be increased by 0.895 points. So it is suggested should aerodrome RadinInten II continues to improve the quality of services to improve passenger satisfaction. Things can be done by airports RadinInten II is to further improve the quality of services that focus on aspects of the airport authorities friendliness and speed of flight information to the passengers, so the aircraft passenger satisfaction has increased. In addition to safety from crime to passengers carried by road adds to the officer - security officer at the airport location and access road exit - entry airports.